2007
DOI: 10.1183/09031936.00150405
|View full text |Cite
|
Sign up to set email alerts
|

Twelve-year longitudinal study of respiratory status in dairy farmers

Abstract: To evaluate respiratory risk in dairy farmers, the present authors conducted a longitudinal study in the Doubs region of France.From a cohort constituted in 1986 (T1), 157 (62.8%) dairy farmers and 159 (63.6%) controls were re-evaluated in 1998 (T3). The study protocol comprised a medical and occupational questionnaire, spirometric tests at both evaluations, and noninvasive measure of blood oxygen saturation with pulse oximetry (Sp,O 2 ) at T3.In 1998, the prevalence of chronic bronchitis was higher in dairy f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
36
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(39 citation statements)
references
References 29 publications
(46 reference statements)
2
36
0
1
Order By: Relevance
“…There have also been previous reports suggesting a higher risk of COPD in dairy farmers compared to unexposed subjects [5,25,26]. In a 12-year longitudinal study, we previously reported that dairy farmers presented a more accelerated decline in FEV1/FVC than controls [25].…”
Section: Discussionsupporting
confidence: 51%
See 1 more Smart Citation
“…There have also been previous reports suggesting a higher risk of COPD in dairy farmers compared to unexposed subjects [5,25,26]. In a 12-year longitudinal study, we previously reported that dairy farmers presented a more accelerated decline in FEV1/FVC than controls [25].…”
Section: Discussionsupporting
confidence: 51%
“…In a 12-year longitudinal study, we previously reported that dairy farmers presented a more accelerated decline in FEV1/FVC than controls [25]. In a study performed in Norwegian farmers, a higher risk of COPD in dairy farmers compared to exclusive crop farmers was observed [5].…”
Section: Discussionmentioning
confidence: 90%
“…The results of two controlled longitudinal studies we conducted in French dairy farmers in 1986 and 1994 were discordant. In the 1986 cohort, we found an accelerated decline in forced vital capacity (FVC) and forced expiratory volume in 1 s (FEV1) in dairy farmers at 5-yr follow-up [15], but these results were not confirmed at the second follow-up 12 yrs after inclusion [16]. This may be due to an improvement in working conditions leading to a decrease in agricultural exposure over time, as suggested by studies in grain elevator workers [17].…”
mentioning
confidence: 82%
“…Some questions have been added to the version used in previous studies [9,16,18]. Working status in 2006 was designated as: ''still working'' (at the same or another job), ''retired'', and ''unemployed or having stopped working for personal reasons''.…”
Section: Questionnairesmentioning
confidence: 99%
See 1 more Smart Citation